(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
The current stage of research of the language system is focused on to study the specifics of language as one of the cognitive subsystems and the role that is assigned to the factor of linguistic forms in the conceptualization of reality. Particular attention is paid to the transmission of results comprehension of the world by man, including different types of assessments and opinions, which provide the implementation of the interpreting function of the language consciousness.